Changes in the Hematological Variables in Pigs Supplemented With Yeast Cell Wall in Response to a Salmonella Challenge in Weaned Pigs - Burdick Sanchez, Nicole C.; Carroll, Jeffery A.; Corley, Jimmie R.; Broadway, Paul R.; Callaway, Todd R. (Frontiers in Veterinary Science, 2019)
Stressors experienced by pigs at weaning that may negatively impact health and productivity. Thus, supplements that enhance pig immunity during the early post-weaned period are of great interest to the swine industry. The objective of this experiment was to evaluate the performance and hematological responses of weaned pigs supplemented with yeast cell wall (YCW) when challenged orally with Salmonella Typhimurium. Weaned pigs were assigned to one of three treatments for 22d (n=13/treatment): Control diet, which was a non-medicated starter diet (Control); Control diet supplemented with YCW at 250 mg/kg BW (YCW250; Phileo Lesaffre Animal Care, Milwaukee, Wisconsin, USA); and Control diet supplemented with YCW at 500 mg/kg BW (YCW500). On d19 blood samples were collected from -6 to 72h relative to oral Salmonella Typhimurium (1 x 106 cfu/pig) challenge. Gain:feed was greater (P=0.01) in YCW250 treatment compared to both Control and YCW500 pigs. Baseline intraperitoneal temperature was greater (P<0.001) in YCW250 pigs than Control or YCW500 pigs. There was a treatment x time interaction for the change in intraperitoneal temperature (P<0.01), post-challenge cortisol, white blood cell counts (WBC), neutrophils, and neutrophil:lymphocyte ratio (P≤0.03). Control pigs had greater (P<0.05) cortisol concentrations than both YCW-supplemented groups at 0h, but Control pigs had reduced (P<0.05) cortisol compared to YCW500 pigs at 24 and 30h post-challenge. Control pigs had greater (P<0.05) WBC counts than both YCW-supplemented groups 6 and 12h post-challenge, and YCW250 pigs had reduced (P<0.01) WBC counts than Control and YCW500 pigs 18h post-challenge. Neutrophil counts were greater (P<0.05) in Control pigs than both YCW-supplemented groups at 6 and 12h post-challenge and were greater (P=0.02) than YCW250 pigs at 18h post-challenge. Lymphocytes were greater (P<0.001) in Control and YCW500 pigs pre- and post-challenge compared to YCW250 pigs. Control pigs had the greatest (P<0.001) monocyte counts compared to YCW treatments. There was no effect of yeast supplementation on fecal shedding or Salmonella counts in the rectum, colon or cecum (P≥0.05). While some differences were observed in intraperitoneal temperature and some hematological variables, data suggests there were minimal effects of yeast supplementation on the acute immune response to Salmonella challenge.